2021
DOI: 10.11361/journalcpij.56.1405
|View full text |Cite
|
Sign up to set email alerts
|

A study on change in dynamics of population and change in intention to choose a residence place by the COVID-19

Abstract: Work from home and online meetings have become spread due to a new lifestyle that prevents infection with the covid-19. With this spread, the workplace and the residence place do not necessarily have to be close to each other, which has an impact on our life. While it has become possible to choose a residence place that is not tied to the workplace. However, if it does not guide local city migration and country life to the right areas, It will become urban sprawl, and there is concern about the widening of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Accordingly, the COVID‐19 pandemic accelerated the traditional movement patterns from the centre to the suburbs within the TMA (Watanabe, 1978 ), indicating a new urban sprawl threat (Tsuboi et al, 2021 ). While the MER of the suburb of the TMA increased, the stream‐specific MERs indicate that the suburbs received much net gain from their centre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the COVID‐19 pandemic accelerated the traditional movement patterns from the centre to the suburbs within the TMA (Watanabe, 1978 ), indicating a new urban sprawl threat (Tsuboi et al, 2021 ). While the MER of the suburb of the TMA increased, the stream‐specific MERs indicate that the suburbs received much net gain from their centre.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the increase of keen interest in residential relocation to provincial areas in TMA reported by the Cabinet Office ( 2021 ), Teng ( 2022 ) reported that young adults’ working environment, income and psychological status were significantly worsened by the COVID‐19 pandemic and that these changes were related to their migration intentions from Tokyo. In addition, Tsuboi et al ( 2021 ) pointed out changes in residential preference from before to after the COVID‐19 pandemic, such as increased interest in residing in the suburbs, in the case of Toyota city, a provincial city.…”
Section: Introductionmentioning
confidence: 99%